Pain level measured with visual analogue scale in patients with hirsutism or hypertrichosis undergoing depilation - Barbara Nieradko-Iwanicka; Jolanta Materna (Kazimierz Wielki University, 2018)
Smooth skin is an attribute of beauty. Hair is a skin appendage. Hirsutism affects 5-10% of the women. There are different methods of excessive hair removal: with creams or foams, shaving, depilation, epilation, waxing, laser treatment or with use of tweezers. The aim of the study was to assess pain level measured with visual analogue scale (VAS 0-10) in persons with hirsutism and hypertrichosis undergoing depilation. An original questionnaire consisting of 7 questions was used as the tool for examining participants. A total of 125 persons participated in the study. Among them were 106 women (84.8%) and 19 were men (15.2%). Mean pain (mean ±SD) due to depilation in women was 3.6 (± 2.26 ;min. 0, max 10) and 3 (±2.8; min. 0.6, max 9.0) in men. Depilation is so painful for some patients, that some of them may require painkillers before it, but this issue should be discussed with the physician.